Tubular carbon membrane for Hydrogen separation: Effect of Pyrolisis condition - Mohd Syafiq, Sharip; Norazlianie, Sazali (Penerbit UMP, 2020)
Hydrogen (H2)-based economy development is expected to create extensive need for efficient collecting strategies of fairly high purity H2. The aim of a H2-selective membrane is to manipulate H2’s high diffusivity characteristics as well as to restrict the outcome of lower solubility. Carbon membranes offer high potential in gas separation industry due to its highly permeable and selective. Therefore, this study aims to investigate the effect of pyrolisis temperature on the gas separation properties. Matrimid 5218 used as a precursor for carbon tubular membrane preparation to produce high quality of carbon membrane via pyrolisis process. The polymer solution was coated on the surface of tubular ceramic tubes by using dip-coating method. Dip-coating technique offer high potential in fabricating defect free carbon membrane. The polymer tubular membrane was then carbonized under argon atmosphere at 600, 700, and 800, and 900oC with heating rate of 2 oC/min. Matrimid 5218-based carbon tubular membranes were fabricated and characterized in terms of its structural morphology, chemical structure, thermal stability, and gas permeation properties by using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and pure gas permeation system, respectively. The highest H2/N2 selectivity of 401.08±2.56 was obtained for carbon membrane carbonized at 800oC with heating rate of 2oC/min